1996
DOI: 10.1002/(sici)1099-0496(199612)22:6<342::aid-ppul2>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

The influence of sleeping position on functional residual capacity and effective pulmonary blood flow in healthy neonates

Abstract: Variation in body position has been shown to affect respiratory function in adults and neonates with and without respiratory illness. At present it remains unclear why respiratory function should be affected by different body positions. We hypothesized that the effect of body weight on the relatively compliant chest wall of the newborn infant in the prone position would cause a reduction in functional residual capacity (FRC) and a compensatory improvement in ventilation/perfusion matching as measured by effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…In contrast, in healthy term born neonates studied in the first 72 h after birth, lung volumes were similar in the prone and supine positions,7 and, among infants studied at a median age of 2.4 months, no significant effect of positioning on oxygenation saturation was noted 8. The latter study population, however, included infants born at term as well as those born prematurely, and, although the infants were all at increased risk of SIDS (previously experienced an acute life-threatening event, inability to fall asleep in their normal position, very premature birth, upper airway obstruction, or had a sibling who had died from SIDS), none had respiratory distress 8.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…In contrast, in healthy term born neonates studied in the first 72 h after birth, lung volumes were similar in the prone and supine positions,7 and, among infants studied at a median age of 2.4 months, no significant effect of positioning on oxygenation saturation was noted 8. The latter study population, however, included infants born at term as well as those born prematurely, and, although the infants were all at increased risk of SIDS (previously experienced an acute life-threatening event, inability to fall asleep in their normal position, very premature birth, upper airway obstruction, or had a sibling who had died from SIDS), none had respiratory distress 8.…”
Section: Discussionmentioning
confidence: 70%
“…None of the infants currently studied were oxygen-dependent when examined post term, but all had had respiratory distress syndrome and half the population had had BPD. Thus, a possible explanation for the differences in position-related effects on oxygen saturation between studies79 is the presence or absence of previous or current lung disease. The impact of positioning on both lung volume and oxygenation has rarely been examined.…”
Section: Discussionmentioning
confidence: 99%
“…FRC is known to increase in spontaneously breathing adult subjects in the prone position, in both awake (19) and anesthetized (18) states, and there are sound theoretical reasons why this should occur (1). To the best of our knowledge, changes in FRC with position have not been reported previously in critically ill children, although a study in spontaneously breathing intubated neonates with mild lung disease failed to demonstrate any increase in FRC despite significant increases in oxygenation (6) and a study in healthy neonates similarly reported no changes in FRC in prone versus supine positions (20). The combination of neuromuscular blockade and positive pressure ventilation may be expected to attenuate position-related changes in lung volumes and mechanics compared with those seen in spontaneously breathing subjects.…”
Section: Discussionmentioning
confidence: 77%
“…Others, however, have suggested that lung volume may be lower in the prone position because of the compressing effect of the infant's body weight on the relatively compliant chest wall. 26 The impact of posture on functional residual capacity of preterm infants at a postconceptional age of near term is unexamined but, in healthy full term infants, no posture related significant changes in either functional residual capacity or effective pulmonary blood flow were shown in the first days after birth. 26 Prone posture also influences the likelihood of gastrooesophageal reflux.…”
Section: Discussionmentioning
confidence: 99%